Exploration and Design of Etno-STEM as a Learning Source in Phytochemistry to Improve Meta-cognitive Skills and Students’ Higher Order Thinking Skills of Environmental Problem (Journal of Wetlands Environmental Management, 2023)
The importance of in-depth exploration and design of Ethno-STEM (Ethno-Science, Technology, Engineering, and Mathematics) as a valuable learning resource within the realm of phytochemistry. This research aims to examine the diversity of local Ethno-STEM culture, design it, and use it as a transformative tool to enhance students' metacognitive and higher-order thinking skills, with a specific focus on addressing pressing environmental issues. In this study, an exploratory qualitative method is used with ethnographic techniques, knowledge extraction from indigenous communities, and laboratory investigations into the phytochemical properties of local flora. In order to learn phytochemistry, we are exploring the potential of Banjar, South Kalimantan's traditional ethno-scientific heritage. The subjects of this research are community leaders and academics who understand Banjar culture and ethnoscience. Data collection was carried out through observation, writing, and interviews. The results of this research show the important role of metacognitive skills in the learning process because they facilitate orientation-representation, planning, monitoring, and evaluation skills. The integration of Ethno-STEM knowledge not only enriches students' understanding of phytochemistry but also encourages the development of higher-order thinking skills for environmental problems (HOTSEP), including critical thinking, problem solving, and developing creative innovations to overcome environmental problems in the field of phytochemistry. The conclusion of this research proves that there is a synergy between indigenous knowledge, Ethno-STEM design for phytochemical learning, the development of metacognitive skills, and higher order- thinking. The results of this research not only contribute to the preservation and appreciation of cultural heritage (Banjar ethnoscience), but also have extraordinary potential for cultivating a generation that is environmentally conscious and able to solve problems.